ANALISIS PENGENDALIAN BAHAN BAKU PADA PABRIK TEMPE JASUN DI KABUPATEN MIMIKA - Endah Tri Cahyani; Tuti Fitriani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to determine the significance of raw material inventory control at the Jasun Factory in Mimika Regency. The method used by researchers is the Economic Order Quantity Method, Descriptive Method, and Comparative Method. The data collection techniques used by researchers are observation, interviews, documentation. The analytical tool used in this research is paired t-test. The results of this study indicate that the control of raw materials for Jasun Tempe Factory in Mimikia Regency has a significant difference in actual profit and EOQ profit at Jasun Tempe Factory